Cardiovascular risk in type 2 diabetes patients - O. D. Ostroumova; I. V. Goloborodova; V. М. Fomina (Кардиоваскулярная терапия и профилактика)
Cardiovascular diseases remain leading cause of high mortality in diabetes patients. The article is focused on the influence of diabetes on cardiovascular risks. The prevalence presented, as the significance of the main and additional risk factors of cardiovascular diseases in the development of macrovascular complications in diabetes. In the context of influence on cardiovascular risks, modern glucose lowering drugs are considered, the safety and efficacy properties. Advantages of dapagliflozin underscored, the novel oral drug of new generation, with safe and prominent antidiabetic effect and ability to correct the main factors of cardiovascular risk (obesity, hypertension).